2019
DOI: 10.1167/iovs.18-25228
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Defocus and Temporal Sensitivity Affect Refractive Development in Guinea Pigs

Abstract: PURPOSE. Environmental light plays an important role in the process of emmetropization. This study investigated how the retina integrates wavelength and temporal signals to regulate eye emmetropization. METHODS. Guinea pigs (n ¼ 220) were randomly divided into 11 groups (n ¼ 20/group) that received different environmental lighting (12:12 light cycle) for 8 weeks: white, green, or blue light at steady, 0.5 or 20 Hz. White-steady group was repeated for each wavelength. Refraction, axial length, and corneal curva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…The signal at low frequencies may reach deeper levels of the anterior chamber, increasing the secretion and slowing down the outflow of fluid in the eye [ 36 ]. Our study showed that VAR at low frequencies are larger than those at high frequencies, and the colour effect is only significant at low frequencies, which is in agreement with the results obtained in animal studies [ 9 , 10 ]. These animal studies showed that colour played a more important role at low temporal frequencies than for high ones, which is an important clue for emmetropisation [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The signal at low frequencies may reach deeper levels of the anterior chamber, increasing the secretion and slowing down the outflow of fluid in the eye [ 36 ]. Our study showed that VAR at low frequencies are larger than those at high frequencies, and the colour effect is only significant at low frequencies, which is in agreement with the results obtained in animal studies [ 9 , 10 ]. These animal studies showed that colour played a more important role at low temporal frequencies than for high ones, which is an important clue for emmetropisation [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that VAR at low frequencies are larger than those at high frequencies, and the colour effect is only significant at low frequencies, which is in agreement with the results obtained in animal studies [ 9 , 10 ]. These animal studies showed that colour played a more important role at low temporal frequencies than for high ones, which is an important clue for emmetropisation [ 9 , 10 ]. For high frequencies, eyes may not be fast enough to accommodate accurately after colour flickers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This flattening effect induces myopic shifts in guinea pigs exposed to blue light and hyperopic shifts in those exposed to green light, as compared with those of corresponding steady conditions. 37 In particular, we were interested in whether retinal DA plays a role in these light responses.…”
mentioning
confidence: 99%